Hemodynamic Changes in Experimentally Envenomed Anaesthetized Rats by Intravenous Injection of Hemiscorpius lepturus Venom - Khalil Pourkhalili; Hossein Fatemikia; Euikyung Kim; Navid Reza Mashayekhy; Naser Mohammadpour Dounighi; Abdollah Hajivandi; Yaghoob Hassan; Ramin Seyedian (Tehran University of Medical Sciences, 2018)
Background: We investigated the hemodynamic changes (Inotropic, chronotropic and arrhythmogenic) in intravenously envenomed anesthetized rats with Hemiscorpius lepturus venom. The neutralizing potencies of different drugs and commercial antivenom were assessed simultaneously. Methods: Different doses of the crude venom (100, 200 and 400μg/rat) were injected during five minutes via the femoral vein and cardiovascular changes were recorded in rats in Razi Institute Corporation, Karaj, Iran in 2017. The drugs (Atropine, lidocaine, propranolol and prazosin) were injected before the venom for determination of the counteracting effects. Different volumes (100, 500 and 1000µl) of the antivenom were pre envenomed to neutralize cardiovascular changes. Results: Temporary hypertension and bradycardia with no arrhythmogenic effects were depicted within twenty minutes. There was a difference in arterial pressure between the venom (400μg/rat) and the vehicle at 8 minutes (114.68±5.1mmHg versus 70.2±4.3mmHg). Elevation of the mean arterial pressure was inhibited by propranolol (2 mg/kg) and neutralized by prazosin (1mg/kg) while lidocaine (4mg/kg) and atropine (1mg/kg) had no effects. Premedication with Iranian commercial antivenom (1000μl) produced surprisingly temporary hypertension compared to the vehicle (140.84±4.5 versus 84.3±3.2). It had no neutralizing properties on blood pressure variation before the venom injection. Volume-expanded hypertension phenomenon was ruled out in a parallel study. Conclusion: This venom has vasoconstrictive effects in rats probably due to the presence of norepinephrine like materials in its content or liberated from adrenal gland inhibited by prazosin premedication. The neutralizing effects of antivenom on venom-induced hypertension are questionable.